Implementación y configuración de seguridad perimetral en el Centro Experimental La Playita de la Universidad Técnica de Cotopaxi extensión La Maná - Quishpe Andrango, Onofre Israel (2017)
The current project is focused on establishing protection mechanisms for the “La Playita” Experimental Center, which has a total perimeter of 371.97 meters, with a one-block length approximation. The objective of the implementation of the IP cameras is to improve the Security of the Experimental Center “La Playita”, through video surveillance that are the best tools for the monitoring of public and private institutions. After the analysis of the area where the application of the project will be carried out, the location will be determined and how each device will be installed to protect it, so that a technical study will be implemented in the Center Experimental “La Playita” of the Technical University of Cotopaxi Extension La Maná. The Network Data Server (NAS) will be located in the Center Experimental “La Playita” with the purpose of ensuring greater security of the data it generates and will also install the monitor that will allow the visualization of the online activities carried out in the Experimental Center “La Playita”, a link will be established with devices of high power in data transfer so that it is feasible the implementation with enough Mbit / s that allows the sharpness in the moment of sending information of video surveillance, taking into account that the Experimental Center Playita already has 20 Mbit/s enabled from its central node of the Matrix (Latacunga), once established the link will have to, connect to a router that will be in charge of the administration of the bandwidth enabled for the Switch to distribute to each point that forms this safety net. It must be taken into account that when performing this type of installation the cameras to be installed become part of the network structure of the Experimental Center “La Playita” as they are constituted as one more device in the Institutional Network. The 7 cameras will be located taking into account the total perimeter and the standards established at “La Playita” Experimental Center to achieve better security through video surveillance, the internal connections will be made by a guided medium such as Category 5 QPcom cable for purity Of construction that it will allow to have greater speed of transfer to the moment of sending and receiving signals from any location. The reception of the data will fall on a DSM operating system, in which it will be installed allowing to control the IP cameras installed, finally we have the NAS, is a storage technology dedicated to sharing the storage capacity of a server with client computers through Of a network (usually TCP / IP), the following devices that have been chosen for the implementation are: Router, Switch, Video Recorder and Mass Storage in a computer, that are the most important and suitable for the implementation of a system of Video surveillance through IP cameras.